DOKTRIN ULTRA VIRES DAN KONSEKUENSI PENERAPANNYA TERHADAP BADAN HUKUM PRIVAT - Ibrahim, Johnny (Faculty of Law, Universitas Jenderal Soedirman, 2011)
An acts is ultra vires when corporation is without authority to perform it under any circumstance or for any purpose beyond the scope of the powers of corporation, as defined by its charter or by law of incorporation. Some countries restrict the application of the doctrine of ultra vires but do not abolish it. Indonesia adopt doctrine of ultra vires in some of its law such as Law No. 40 of 2007 concerning Limited Liability Company and Law No. 25 of 2003 concerning Anti Money Laundering. The provisions of ultra vires doctrine has impact to other legal person than Limited Liability Company. Key words: ultra vires, extra vires, intra vires